Can we predict medium term mortality from transvenous lead extraction pre-operatively?. (2018) - Elamin, Nadir; M, Khan; R, Bowes; J, Sahu; P, Sheridan; D, Rogers; N, Kyriacou; N, Kelland; N, Lewis
No abstract available